Penurunan Kadar Cr+3 [Kromium(III)] dan TSS (Total Suspended Solid) Pada Limbah Cair Laboratorium Dengan Penggunaan Metode Presipitasi - Isma Avessa; Bohari Yusuf; Alimuddin Alimuddin (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2016)
The aims of this research was to decrease the level chromium and TSS in the laboratory wastewater liquid sample PT SUCOFINDO by using calcium hydroxide and sodium hydroxide. Precipitation process was done by reacting the wastewater sample and solution Ca(OH)2 0,2 and NaOH 1 M at pH variation 7, 8, 9, 10 and 11, then allowed to settle for 24 hours and established the optimal pH at both solution was used in the precipitation process. Analysis content of Cr metal at this research using AAS instrument and analysis for content of TSS in this research using gravimetric method. The optimal pH precipitation to decrease Cr metal and TSS level is 8 in each of the solution used. Cr metal level after precipitation using Ca(OH)2 solution at pH 8 is 0.0901 mg/L and TSS level is 0.005 mg/L. Cr metal level after precipitation using NaOH at pH 8 is 0.0935 mg/L and TSS level is 0.008 mg/L. If compared with level decrease of Cr metal and TSS in laboratory wastewater using Ca(OH)2 and NaOH solution, and found the effectiveness of solution that have better efficiency to reduce levels of Cr and TSS in the low concentration is calcium hydroxide.